Efficient mapping of transgene integration sites and local structural changes in Cre transgenic mice using targeted locus amplification. Issue 8 (4th January 2017) - Cain-Hom, Carol; Splinter, Erik; van Min, Max; Simonis, Marieke; van de Heijning, Monique; Martinez, Maria; Asghari, Vida; Cox, J. Colin; Warming, Søren
Abstract: Cre/LoxP technology is widely used in the field of mouse genetics for spatial and/or temporal regulation of gene function. For Cre lines generated via pronuclear microinjection of a Cre transgene construct, the integration site is random and in most cases not known. Integration of a transgene can disrupt an endogenous gene, potentially interfering with interpretation of the phenotype. In addition, knowledge of where the transgene is integrated is important for planning of crosses between animals carrying a conditional allele and a given Cre allele in case the alleles are on the same chromosome. We have used targeted locus amplification (TLA) to efficiently map the transgene location in seven previously published Cre and CreERT2 transgenic lines. In all lines, transgene insertion was associated with structural changes of variable complexity, illustrating the importance of testing for rearrangements around the integration site. In all seven lines the exact integration site and breakpoint sequences were identified. Our methods, data and genotyping assays can be used as a resource for the mouse community and our results illustrate the power of the TLA method to not only efficiently map the integration site of any transgene, but also provide additional information regarding the transgene integration events.